Impact of biochar on the fungal decay resistance of hemp-polylactic acid composites against wood basidiomycetes - Zouari, Mariem; Mikuljan, Marica; Schwarzkopf, Matthew (Frontiers in Materials, 2023)
Natural fibers reinforced composites represent a sustainable alternative to synthetic polymer-based materials. However, natural fibers are susceptible to fungal degradation which reduces the lifespan of the composites in use. The objective of this study was to investigate the effect of biochar (BC) on improving the resistance to fungal decay of polylactic acid (PLA) and hemp-PLA composites. The influence of incremental BC loadings (0, 5, 10, and 20 wt%) on physiological and morphological properties of the composites was evaluated. Weight loss, color stability, microscopic observations, and water contact angle measurements were performed during and after 5-months of exposure to white (Trametes Versicolor) and brown (Fomitopsis Betulina) rot fungi. We found that the addition of 10 wt% BC decreased the total weight loss in PLA and hemp-PLA composites by 93% and 34%, respectively in the case of exposure to white rot and by 66% and 83%, respectively in the case of exposure to brown rot as compared to neat PLA. BC addition improved the color stability of the composites. The color change in hemp-PLA samples loaded by 10 wt% of BC decreased by 44% and 37%, in the case of exposure to white and brown rots, respectively as compared to hemp-PLA reference. Moreover, samples containing BC (5 wt% and 10 wt%) had higher gloss after the decay test among all other samples. Micrographs revealed that white and brown rots invaded the surface of the composites at the beginning of the incubation period and then accessed the interior of the materials. Micro-cracks occurred in samples containing hemp fibers which enabled the fungi to invade the internal structure of the composites. At the same time, fungi grew on the surface of samples without hemp fibers except for PLA with 20% BC content which had a porous surface that allowed fungi to access the interior. The hydrophobicity of all samples increased during the first 3 months of the incubation and then decreased again by the end of the incubation as the surface of the composites started to be damaged. Our study provided a novel direction of BC as an organic additive in bio-composites. Uncovering the potential of BC in improving the resistance to fungal decay of natural fibers-reinforced composites paves the way for BC’s utilization as a renewable additive in various applications such as bio-based packaging materials.